BOND STUDIES OF CFRP STRENGTHENED STEEL PLATES EXPOSED TO SERVICE TEMPERATURE - LYE, HUI LI (2021)
Emerging to the new technology, carbon fiber reinforced polymer (CFRP) has been introduced to rehabilitate and strengthen steel structures using adhesive agent.